The Republic of Buryatia population malignant neoplasms rate - T. N. Chimitdorzhieva (Сибирский научный медицинский журнал, 2021)
The degree of morbidity of the population of the Republic of Buryatia with malignant neoplasms without subdivision by localization from 1996 to 2019 was analyzed according to the data of the Republican Clinical Oncological Dispensary. Material and methods. The data on the incidence of malignant neoplasms in the population of municipalities of the Buryat Republican Clinical Oncological Dispensary, expressed in intensive («rough») indicators (PI) per 100 thousand population (ppm, 0/0000) have been analyzed. The zoning of the incidence of the population has been based on the approach of medico-geographical typification of the territory. The range of indicators of the incidence of cancer in the population served as the basis for identifying four types of territories by the levels of cancer pathology: low – medium – high – very high. The dynamics of morbidity was analyzed by the average indicators of four 5-year periods (1996–2000, 2001–2005, 2006–2010, 2011–2015) and one 4-year period (2016–2019). Cartographic processing of the material was performed using Paint.NET. The comparison of morbidity in 21 municipal districts has been carried out. In period 1, there were 4 districts with low pathology (90–134 people): Okinsky, Muisky, Tunkinsky, Zakamensky districts, and with very high pathology (225–277 cases) – 4 districts: Pribaikalsky, Kabansky, Zaigraevsky, Bauntovsky. In the second period, the Okinsky, Tunkinsky, Dzhidinsky districts had low rates (100–158 cases), and the North-Baikalsky, Ivolginsky, Selenginsky, Kurumkansky, Mukhorshibirsky districts had very high level (257 and more). In the third period: low incidence rate (100–150 cases) has been determined in Muisky, Kizhinginsky districts, very high rate (274–331 cases) – in Bauntovsky, Kabansky, Zaigraevsky, Tarbagataisky districts. In the fourth period: low pathology rate (155–212 people) was in Okinsky, Zakamensky, Muisky, Eravninsky, Ivolginsky districts, very high level (329 cases) was in Bauntovsky district. In the last four years: low case rate (138–204) was only in Okinsky district, very high pathology level (339–405 people) was in 5 districts, to Bauntovsky, Kabansky, Pribaikalsky districts were added the northern districts: Severo-Baikalsky and Barguzinsky. Territories with high indicators of malignant neoplasms include: Pribaikalsky (393.5 ± 39.9 0/0000), Kabansky (397.5 ± 21.9 0/0000), Zaigraevsky (318.2 ± 13.6 0/0000), Bauntovsky (403.6 ± 51.6 0/ 0000); with reduced ones – Zakamensky (241.1 ± 17.4 0/0000), Tunkinsky (215.9 ± 6.8 0/0000), Eravinsky (214.3 ± 16.5 0/0000), Okinsky (137.8 ± 6.1 0/0000) districts. The malignant neoplasms incidence of the population of the Republic Buryatia is high, and it is growing every year.